1977
DOI: 10.1021/j100529a005
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of hydroxycyclohexadienyl radicals of methylated benzenes to cation radicals in acid media

Abstract: Publication costs assisted by Ris4 National Laboratory Formation of radical cations from the OH adducts of methylated benzenes in acidic aqueous solutions is demonstrated. The radical cation is formed as an intermediate species in the water elimination reaction in which the OH adduct is transformed into the corresponding methylbenzyl radical. The radical cations are also produced in neutral aqueous solution by reacting SOf radical ions with the methylated benzenes. The cations have two absorption bands, an UV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 8 publications
1
47
0
Order By: Relevance
“…For both 9-MA and 1-MeNap, we observed sharp features in the 675- to 750-nm region, while for Tol, a sharp peak at 450 nm was observed. Notably, the radical cation features for all the three molecules were slightly redshifted by ~10 to 20 nm from their respective free-solution absorption maxima, providing evidence for confinement of the radical cations ( 42 , 43 ). The cage-incarcerated radical cationic state of the aromatic substrates was observed to decay in a picosecond time scale to form the corresponding neutral benzyl radicals after donating a proton to the solvent water molecule since it is an exergonic process ( 41 ).…”
Section: Resultsmentioning
confidence: 91%
“…For both 9-MA and 1-MeNap, we observed sharp features in the 675- to 750-nm region, while for Tol, a sharp peak at 450 nm was observed. Notably, the radical cation features for all the three molecules were slightly redshifted by ~10 to 20 nm from their respective free-solution absorption maxima, providing evidence for confinement of the radical cations ( 42 , 43 ). The cage-incarcerated radical cationic state of the aromatic substrates was observed to decay in a picosecond time scale to form the corresponding neutral benzyl radicals after donating a proton to the solvent water molecule since it is an exergonic process ( 41 ).…”
Section: Resultsmentioning
confidence: 91%
“…[3][4][5][6] The estimated steady-state concentration of HO under fuel cell operating conditions is on the order of 10 À16 M. 7 Recently, we studied the reaction of HO with a model compound of a polystyrenesulfonic acid based ionomer, an oligomer with an average molecular weight of 1100 Da, poly(sodium styrene sulfonatew) (PSSS-1100) in oxygenated solution. 8 90% of HO react by addition to the aromatic ring, forming a HO-adduct.z At low pH, water elimination by reaction of protons with HO-adducts yields a radical cation, [9][10][11][12] (reaction (1)), as follows from electron paramagnetic resonance spectroscopy, UV/Vis-spectrophotometry, and conductivity measurements. 9,11,13,14 ð1Þ By means of electron paramagnetic resonance spectroscopy, Hu¨bner and Roduner observed that the reaction of HO with toluenesulfonate-used as a model compound for fuel cell membranes-yields benzyl radicals at pH 0.5-1.5, analogous to reaction (1).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of acid in inducing deprotonation rather than decarboxylation may then be interpreted in several ways. First, if decarboxylation occurs via direct electrontransfer (from C0,H or C0,-to the ring) then it would be anticipated that this would occur more readily from the carboxylate anion (a radical-zwitterion) (10) than from (9). Secondly, it is conceivable that the overall electron-transfer occurs via the formation and decomposition of a bicyclic species, e.g.…”
Section: Resultsmentioning
confidence: 99%